Transição de fase e um critério para interface de perímetro mínimo - Ribeiro, Wagner Xavier (2019)
Using phase transition theory we will present a criterium to determining minimal interfaces. In order to do this, we will look at the results of geometric measure theory as prerequisite and to conclude the work, we will present a beautiful argument due to MODICA to prove a well known conjecture of GURTIN.